ANALYTICAL HIERARCHY PROCESS APPROACH ON CONSUMER PREFERENCE OF TOYOTA AGYA, DAIHATSU AYLA, HONDA BRIO IN MANADO - Handoko, Agnes Maria (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The automobile industry in Manado has grown rapidly. So many type of car launched to fulfill the customer need for their daily mobility. Follow the current situation, where price of fuel increasing continously, and pollution level has increase day by day, the car producer react by launched a several type of small car. The purpose of this research are to determine which criteria in the small car is mostly selected by customers and to define which small car that customers like the most. This research used Analytical Hierarchy Process (AHP) to compare each small car. The respondent is 40 people and this research using purposive sampling.The respondent of this research is the people that has an experience ride or drive this three small cars. The result shows that Toyota Agya become the most preferred small car by the consumer, followed by Daihatsu AylaÂ  and Honda Brio in the last place. Thus, recommendation for Daihatsu Ayla and Honda Brio management as the competitors of Toyota Agya, have to improve their vehicle performance,in order to attract more customer, especially for some criteria that make customer tend to choose Toyota Agya. Keywords: consumer preference, small car, analytical hierarchy process.